Socio-educational factors associated to perception of research among stomatology students in a Cuban university - Ibraín Enrique Corrales-Reyes; Yasmany Fornaris-Cedeño; Leonardo Valdés-Gamboa; Alberto Juan Dorta-Contreras; Christian R. Mejia (Universidad de Concepción., 2019)
Introduction: Conducting research at the undergraduate level is essential to prepare future professionals for the process of properly channeling their scientific interest and provision of care. However, the factors influencing the degree of participation of students in research are unknown. Aim: To determine the socio-educational factors associated with the perception of research among stomatology students in a Cuban university. Materials and Methods: Cross-sectional analytical study conducted on 166 stomatology students. Participants received an anonymous, validated and self-administered questionnaire designed to collect information on the perception of scientific research within the educational spectrum, which included elements related to writing, participation, scientific publication and the interest of pursuing a career in research. Using associative statistics, those who had an overall positive perception of research were considered interested and were assessed according to socio-educational variables. Results: Students showed a positive perception of scientific research; however, when asked if they wanted to pursue a career in research, only 61.4% responded affirmatively. This positive perception increases with the progression of academic years (p<0.04), is higher in males (p=0.030) and in students who perform assistantships in core courses (p=0.001). Conclusions: There is a positive perception of scientific research, which tends to be intensified by academic progression and other factors. This must be considered by educational institutions in order to generate strategies as a response.